Application of methane and hydrogen-based breath test in the study of gestational diabetes mellitus and intestinal microbes. (June 2021) - Zhang, Miao; Xu, Yajuan; Zhang, Jingzhe; Sun, Zongzong; Ban, Yanjie; Wang, Biao; Hou, Xiaofeng; Cai, Yanjun; Li, Jingjing; Wang, Mengqi; Wang, Wentao
Abstract: Objective: Gestational diabetes mellitus (GDM) is a common complication of pregnancy. The purpose of this study was to compare the incidence of small intestinal bacterial overgrowth (SIBO) in patients with GDM and the control group by methane and hydrogen lactulose breath test (LBT), and to explore its relationship with inflammation, vitamins, and the outcomes of maternal and child. Methods: LBT was detected in 220 GDM patients, 160 pregnancy control patients and 160 pre-pregnancy control patients. The fasting blood glucose, white blood cells, vitamin A, D, E, neonatal weight, neonatal blood glucose and so on were compared and analyzed. Results: There was no statistical significance in the general data of the three groups. The proportion of abdominal distension in the GDM group was higher than that in the other two groups (P < 0.001). The positive rates of SIBO + in GDM group, gestational control group and pre-pregnancy control group were 54.55%, 27.50% and 14.38%, respectively. The average abundance of hydrogen and methane in GDM group was significantly higher than that in control group at each time point. In the GDM group, SIBO + subjects had higher levels of fasting blood glucose, glycoglycated hemoglobin, C-reactive protein, neonatal weight, and lower levels of vitamin D and neonatal blood glucose (P < 0.001). Conclusion: Patients with GDM have a high incidence of SIBO, and SIBO may further increase their blood glucose by affecting inflammatory response and vitamin level, and even affect the outcome of mother and child.